Effect of Taxpayer Ownership Obligations, Taxation Understanding and Personal Taxpayer Awareness of Taxpayer Compliance - Ida Ida; Jenni Jenni (Komunitas Dosen Indonesia, 2019)
The research aims to analyze the influence of the obligation to have tax number, understanding of taxation and awareness of taxpayers against taxpayer compliance. The respondents in this study is the tax payers private person residing in housing Regensi II Tangerang. Some previous research on taxpayer compliance shows the results of the same and also different. Therefore, other studies conducted to test a theory about taxpayer compliance. The population inthis research as much as 133 people. A method or technique of sampling conducted in this study was purposive sampling with counting use the formula slovin, so it can be determined the number of taxpayers private people who became the reseacrh as many as 100. The data collected werw processed using a program SPSS version 24.0, with validity test, reliability test, descriptive statistical test, classical assumption test, multiple linear regression analysis, and the last with a hypothesis test. The results of the research that has been processed shows that the value of significant obligation to have tax number is 0,000, significant value understanding of taxation is 0,048, and significant awareness of taxpayers is 0,015. So the results of the study showed that the level of the obligation to have tax number, understanding of taxation and awareness of taxpayers significant effect against a compliance by tax payers